Articulation of Indigenous Traditions in Tourism: A Case Study of Kenduri Sko in Kerinci, Jambi - Mufdil Tuhri; Deki Syaputra ZE (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This study examines the practice of Kenduri Sko, one of the local traditions of the Kerinci people that has been rarely practiced. Since 2017, the government of Sungai Penuh City took over the management of the practice turning it into an annual tourist attraction called as the Festival of Kenduri Sko. This paper argues that the articulation of this indigenous tradition, and its combination with religion and tourism has stimulated the attempt to preserve indigenous practices through a strategic relationship between government officials and local actors. To show how this the case, we discuss the theory of indigenous religions and the theory of articulation. We use qualitative methods and conducted field studies on the Kerinci People who live in Sungai Penuh City. The article concludes that this kind of articulation has succeeded in placing indigenous peoples as the main actors of the initiative, where the government plays a supporting role in preserving the traditions. This article also recommends a synergistic relationship between the local government and the community to maintain the tradition through various events such as festivals, art performances, and other such projects. Penelitian ini mengkaji praktek Kenduri Sko sebagai salah satu tradisi lokal masyarakat Kerinci yang sudah jarang dilakukan. Sejak tahun 2017, Pemerintah Kota Sungai Penuh mengambil alih praktik tersebut sebagai ikon pariwisata yang disebut dengan Festival Kenduri Sko yang diadakan setiap tahun. Artikel ini berpendapat bahwa artikulasi adat istiadat, agama, dan pariwisata telah mendorong upaya pelestarian praktik adat melalui hubungan strategis antara pejabat pemerintah dan aktor lokal. Untuk membangun argumen ini, artikel ini mengelaborasi teori agama leluhur dan teori artikulasi. Artikel ini menggunakan metode kualitatif serta melakukan studi lapangan terhadap Masyarakat Kerinci yang berdomisili di Kota Sungai Penuh. Artikel ini menyimpulkan bahwa artikulasi semacam itu telah berhasil menempatkan masyarakat adat sebagai aktor utama dimana peran pemerintah sebagai aktor pendukung dalam pelestarian tradisi. Artikel ini juga merekomendasikan adanya hubungan yang sinergis antara pemerintah lokal dan masyarakat untuk mempertahankan tradisi luluhur melalui berbagai macam acara seperti festival, pergelaran seni dan semacamnya